1991
DOI: 10.1128/iai.59.7.2382-2388.1991
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an extracellular 29-kilodalton phospholipase C from Listeria monocytogenes

Abstract: We purified and characterized an extracellular phospholipase produced by Listeria monocytogenes. This enzyme was separated as a homogeneous protein of 29 kDa by chromatography on DEAE-52 cellulose and Bio-Gel P100 columns. It is a zinc-dependent phospholipase C (PLC) that is mainly active at pH 6 to 7 and expresses lecithinase activity and a weaker sphingomyelinase activity. The exoenzyme also hydrolyzed phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, and sphingomyelin but not phosphatidylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(83 citation statements)
references
References 38 publications
3
79
0
1
Order By: Relevance
“…a. This residual activity is attributable to the wide-substraterange phospholipase C, PlcB (or lecithinase), which has a weak SM-hydrolysing activity (Geoffroy et al, 1991) and is overproduced by wild-type L. ivanovii (Ripio et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…a. This residual activity is attributable to the wide-substraterange phospholipase C, PlcB (or lecithinase), which has a weak SM-hydrolysing activity (Geoffroy et al, 1991) and is overproduced by wild-type L. ivanovii (Ripio et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…7A). Several experiments have shown that PC and Sph can also be substrates for PC-PLC (Geoffroy et al, 1991;Goldfine et al, 1993;Montes et al, 2004). Therefore, in theory PC-PLC should be able to attack not only the inner membrane, but also the outer membrane of the spreading vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…The hemolytic activity assay was performed as described previously (Glomski et al, 2002): bacterial supernatants were treated with 5 mM DTT, serially diluted in phosphate-buffered saline (PBS), and incubated with 0.5% sheep red blood cell suspension (NovaMed ® ); hemolysis was measured by following the change in absorbance at 540 nm. The PI-PLC activity assay was adapted from Geoffroy et al (1991): 1 ml of sodium-cholate (58 mM), CaCl2 (10 mM) and 0.036 g phosphatidyl-inositol (P6636; Sigma ® ) were mixed with 7 ml NaCl (0.15 M). One hundred microliters of the assay solution was then mixed with 100 μl of bacterial supernatants and incubated in a plate reader at 37°C for 10 h, following turbidity assessment at 510 nm.…”
Section: Analysis Of Llo and Plca Activitymentioning
confidence: 99%
“…L. monocytogenes invades host cells either passively via phagocytosis or actively by expressing surface proteins that induce bacterial internalization (Cossart, 2011). Once inside the cell, L. monocytogenes is initially contained in a vacuole from which it rapidly escapes by expressing the pore-forming cytolysin listeriolysin O (LLO), two additional phospholipases, PlcA and PlcB, and components of the Com system (Mengaud et al, 1987;Goebel et al, 1988;Portnoy et al, 1988;Geoffroy et al, 1991;Leimeister-Wachter et al, 1991;Rabinovich et al, 2012). In the host cell cytosol, L. monocytogenes replicates and gains mobility via polymerization of host actin filaments, enabling the bacteria to spread from cell to cell without being exposed to the extracellular environment (Tilney and Portnoy, 1989).…”
Section: Introductionmentioning
confidence: 99%